PENERAPAN METODE FUZZY SUGENO DALAM PENENTUAN KONDISI TRAFO DI PLN ULP BLITAR - Fuad Hasan Nawawi; Zunita Wulansari; Wahyu Dwi Puspitasari (STKIP PGRI Situbondo, 2025)
Transformers play a crucial role in the electricity distribution system, and their failures may significantly impact the reliability of power supply. This study aims to analyze the health condition of transformers at PLN ULP Blitar using the Fuzzy Sugeno method, implemented in a web-based system (PHP and MySQL). This approach enables automatic evaluation of hundreds of transformer assets more efficiently compared to manual monitoring. Validation was conducted using the Fuzzy Logic Toolbox in MATLAB to ensure accuracy and reliability. The results indicate that the application of Fuzzy Sugeno logic provides fast, accurate, and structured evaluations of transformer conditions, supporting early detection of potential failures. Therefore, this method can serve as an effective decision-support tool for optimizing asset management and maintaining the reliability of electricity distribution in PLN ULP Blitar.